Petrarchs Triumphi in the British Isles (MODERN HUMANITIES RESEARC, 2020)
This edition argues that Petrarch's text has been neglected by modern scholarship in favour of the translations of the Canzoniere, while it can be shown that the Triumphi enjoyed a much earlier and much more durable fame in Europe as well as in the British Isles, being translated at least twice in its entirety, with individual books and smaller sections being translated or adapted a number of times. Critical editions of the translations are accompanied by analysis of the reception of Petrarch's work in the British Isles, looking at the circulation of the book in the original Italian and in the various French translations, as well as at the use that is made of the Triumphi motifs not only in literature, but in paintings, music, etc.